A Compliance Risk Management In Islamic And Conventional Banking: A Systematic Literature Review And Research Agenda - Dede Nurdiansyah (Scieclouds Publishing, 2026)
This study systematically reviews the development of compliance risk management in Islamic and conventional banking by synthesizing scholarly evidence published between 2015 and 2025. Using a Systematic Literature Review approach guided by the PRISMA framework, this review analyzes 107 studies collected from Scopus and the Watase database. The analysis applies thematic synthesis, supported by the TCCM and CIMO frameworks, to identify the dominant theories, contexts, characteristics, methodologies, mechanisms, and outcomes discussed in the literature. The findings show that compliance risk management has evolved from a narrow regulatory obligation into a multidimensional governance capability shaped by regulatory pressure, corporate governance, Shariah governance, technological capability, organizational culture, and stakeholder expectations. Four major thematic clusters emerged from the reviewed studies: regulatory compliance and banking risk management, Shariah compliance and Shariah governance, corporate governance and internal control, and digital transformation in compliance practices. The review also finds that existing research is geographically concentrated in Malaysia, Indonesia, South Asia, and GCC countries, reflecting the institutional maturity of Islamic finance and dual banking systems in these regions. Although many studies emphasize the positive role of governance and compliance mechanisms in improving stability, legitimacy, and performance, the evidence also indicates that compliance may generate operational costs and rigidity when implemented only as a formal requirement. Furthermore, digital transformation, including fintech, regtech, artificial intelligence, cybersecurity, and digital monitoring tools, remains an emerging but underdeveloped area. This review contributes by offering an integrative synthesis and proposing future research directions on AI-driven compliance, ESG-Shariah integration, and cross-jurisdictional regulatory harmonization.